Anxiety, Stress and Depression in COVID-19 Survivors From an Italian Cohort of Hospitalized Patients: Results From a 1-Year Follow-Up - Gramaglia, Carla; Gattoni, Eleonora; Gambaro, Eleonora; Bellan, Mattia; Balbo, Piero Emilio; Baricich, Alessio; Sainaghi, Pier Paolo; Pirisi, Mario; Binda, Valeria; Feggi, Alessandro; Jona, Amalia; Marangon, Debora; et al. (Frontiers in Psychiatry, 2022)
Background Mental health-related symptoms can persist over time beyond the most common respiratory clinical features of COVID-19. A recent meta-analysis underlined that mental health sequalae may be relevant for COVID-19 survivors and reported the following prevalence rates: 20% for post-traumatic stress disorder, 22% for anxiety, 36% for psychological distress, and 21% for depression. In the context of a multi-disciplinary follow-up project, we already investigated the mid-term (4 months) psychiatric outcomes in a sample of COVID-19 survivors. Patients were re-assessed after 1-year since hospital discharge. Methods Follow-up conducted after 1 year involved 196 individuals recovered from COVID-19. Patients were assessed with a multi-disciplinary approach; including both a clinical interview performed by an experienced psychiatrist, trained in the use of the Mini-International Neuropsychiatric Interview (MINI) to assess the presence of anxiety, stress, and depressive symptoms and the following self-administered questionnaires: Beck Anxiety Inventory, Beck Depression Inventory-II, Resilience Scale for Adults, Impact of Event Scale, and COVID-19 Peritraumatic Distress Index (CPDI). Results Anxiety (p < 0.0001) and depressive (p < 0.0003) symptoms registered at the clinical interview showed a significant improvement from the 4 to 12-months follow-up. Logistic regression model showed that female gender (p = 0.006), arterial hypertension (p = 0.01), obesity (0.04), anxiety (p < 0.0001), and depressive (p = 0.02) symptoms at 4-months follow-up were associated with persistence of anxiety symptoms at 12 months. At logistic regression analysis female gender (p = 0.02) and depressive symptoms at 4-months follow-up (p = 0.01) were associated with depressive symptoms after 12 months. Conclusion Severity of the disease in the acute phase, in this study, was not a determining factor in identifying subjects at risk of developing clinically relevant anxiety and depression as a consequence of COVID-19 disease. Findings from the logistic regressions suggest that the factors most affecting depression and anxiety in COVID survivors after 12 months were female gender, the presence of anxiety and depression after 4 months and some physical symptoms, not necessarily COVID-related. Impact of infection and consequent hospitalization for COVID-19 did no longer represent a relevant issue for depressive symptoms, compared to other general factors.